Inhibition of T-cell responses by feeding peptides containing major and cryptic epitopes: studies with the Der p I allergen. - Hoyne, G F (1994)
H-2b mice respond to the 222 residue allergen Der p I by producing T cells sensitized to the dominant epitopes encompassed in peptides 21-49, 78-100, 110-131 and 197-212. Immunization with the synthetic peptides 120-143 and 144-169, however, revealed cryptic epitopes which could sensitize T cells for responses to the respective peptides and, providing splenic adherent cells were added to lymph node cultures, to the whole allergen. It is shown that feeding recombinant fusion peptides can markedly inhibit the ability of the whole antigen to immunize mice, as measured by the in vitro interleukin-2 (IL-2) and granulocyte-macrophage colony-stimulating factor (GM-CSF)/IL-3 release on stimulation with protein or peptides, although inhibition measured by IL-2 release was more marked. The inhibition extended to epitopes other than those in the fusion peptides used for feeding. Thus feeding peptide 101-154 inhibited responses to 110-131 and 78-100. Fusion peptides 1-14 and 188-222 did not inhibit responses, although 188-222 did contain an epitope. Inhibition was also obtained when mice were fed a fusion containing the cryptic epitope 144-169. The ability of peptides containing the cryptic epitopes to inhibit responses has significant implications for peptide-based immunotherapy.